Effects on surface-enhanced Raman scattering from copper nanoparticles synthesized by laser ablation. Issue 3 (3rd March 2020) - Rawat, Rajesh; Tiwari, Archana; Singh, Manish Kumar; Mandal, R. K.; Pathak, A. P.; Tripathi, Ajay
Abstract : In this work, we report the synthesis of Cu nanoparticles (NPs) by laser ablation technique using 532 nm and 1064 nm wavelength in ethylene glycol. The optical and morphological studies of as-prepared NP colloids were characterized using UV–Visible absorption, photoluminescence spectrometers and transmission electron microscope (TEM) techniques. Cu NPs synthesized at 532 nm and 1064 nm were spherical with an average size of 3.2 ± 0.1 nm and 4.3 ± 0.1 nm respectively. Furthermore, surface-enhanced Raman scattering (SERS) studies were performed on methylene blue (MB) using Cu NPs as SERS platform. In addition, the effects of size, shape and localized surface plasmon resonance (LSPR) of Cu NPs as well as the Raman excitation wavelength used for SERS measurement were investigated and discussed to give insight into the factors affecting their SERS enhancement factor.